The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1182/blood-2002-10-3058
|View full text |Cite
|
Sign up to set email alerts
|

Ligation of Siglec-8: a selective mechanism for induction of human eosinophil apoptosis

Abstract: IntroductionEosinophils, through release of preformed and newly generated mediators, are considered key effector cells in several diseases. Their recruitment and activation are regarded as central to the pathophysiology of allergic disorders, including asthma. [1][2][3] Besides selective migration, increased cell survival and decreased apoptosis have been proposed as mechanisms contributing to tissue-specific accumulation of these inflammatory cells. 4 Hence, therapeutic efforts in the area of allergic inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
265
3
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(279 citation statements)
references
References 44 publications
3
265
3
5
Order By: Relevance
“…Ligand-mediated activation of receptors can be mimicked by receptor ligation using specific mAbs, a strategy that has been commonly used for the study of granulocyte death-inducing receptors, including Fas, TNFR1, TNFR2, TRAIL receptors, Siglec-8, Siglec-9, and CD44 (22,24,30,(33)(34)(35). In agreement with our hypothesis, we observed that mAb-mediated ligation of FcaRI led to significant death of peripheral blood neutrophils from healthy donors in a time-dependent ( Fig.…”
Section: Differential Susceptibility Of Primed and Resting Neutrophilsupporting
confidence: 89%
“…Ligand-mediated activation of receptors can be mimicked by receptor ligation using specific mAbs, a strategy that has been commonly used for the study of granulocyte death-inducing receptors, including Fas, TNFR1, TNFR2, TRAIL receptors, Siglec-8, Siglec-9, and CD44 (22,24,30,(33)(34)(35). In agreement with our hypothesis, we observed that mAb-mediated ligation of FcaRI led to significant death of peripheral blood neutrophils from healthy donors in a time-dependent ( Fig.…”
Section: Differential Susceptibility Of Primed and Resting Neutrophilsupporting
confidence: 89%
“…Indeed loss of inhibitory receptor function has been implicated in a number of diseases that involve cellular activation, including autoimmunity [45] and allergy [46]. Using antibody cross linking, we have also examined the possibility that MICL may be involved in apoptosis, as has been demonstrated for other inhibitory receptors [47][48][49], but despite considerable effort we were unable to demonstrate a role for MICL in this process (data not shown). It seems likely therefore that the functions of this receptor will only be clearly established following the identification of its ligand.…”
mentioning
confidence: 92%
“…This suggests that the natural function of CD33-related siglecs is to modulate leukocyte activation, possibly in an analogous fashion to the inhibitory receptor CD22/ siglec-2 on B cells [7][8][9]. Other studies have indicated that CD33-related siglecs may potentially regulate leukocyte proliferation and apoptosis through unknown mechanisms [10][11][12].…”
Section: Introductionmentioning
confidence: 99%